2022
DOI: 10.3390/ijms23052500
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 23 and Osteoporosis: Evidence from Bench to Bedside

Abstract: Osteoporosis is a chronic debilitating disease caused by imbalanced bone remodeling processes that impair the structural integrity of bone. Over the last ten years, the association between fibroblast growth factor 23 (FGF23) and osteoporosis has been studied in both pre-clinical and clinical investigations. FGF23 is a bone-derived endocrine factor that regulates mineral homeostasis via the fibroblast growth factor receptors (FGFRs)/αKlotho complex. These receptors are expressed in kidney and the parathyroid gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Almost all studies so far have found no correlation between FGF23 and BMD in humans [ 14 ]. A recent review concluded that only supraphysiological levels of FGF23 cause abnormal bone formation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Almost all studies so far have found no correlation between FGF23 and BMD in humans [ 14 ]. A recent review concluded that only supraphysiological levels of FGF23 cause abnormal bone formation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in women with PCOS at increased risk of cardiovascular disease, assessed according to the Androgen Excess and PCOS Society consensus (71), FGF23 was 40% higher and vitamin D 32% lower compared with women with PCOS not at increased cardiovascular disease risk (70). Beyond levels of bone-related blood markers, BMD was not assessed in this study, which would be a fruitful area for further investigation given the inconsistent clinical evidence regarding the effects of FGF23 on bone mass and fragility fractures in non-PCOS cohorts (the elderly and patients with chronic kidney disease) (72). Overall, whether FGF23 is an important putative factor in bone health in PCOS, especially in women with obesity where FGF23 levels are higher, remains to be determined.…”
Section: Bone Metabolismmentioning
confidence: 97%
“…The formation and development of osteoporosis are regulated by various bone-related transcription factors and genetic factors at the molecular level, including transforming growth factor β (TGF- β ), parathyroid hormone (PTH), and fibroblast growth factor (FGF) [ 8 , 9 , 10 ]. These bone-related growth factors have direct or indirect physiological and pathological regulatory effects on osteoblast differentiation and the activities of osteoblasts and osteoclasts through autocrine/paracrine mechanisms [ 11 ].…”
Section: Bone Growth Factorsmentioning
confidence: 99%